O pewnych pożytkach z nudy w etyce - ZDRENKA, Marcin T. (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The focus of the article is the question of boredom in the context of ethics. Starting with Josef Brodsky’s classical essay on the praise of boredom, considered as a positive attitude of human life, and having adopted this affirmative perspective, the author develops some motifs already present within moral reflection. Thus the article offers a certain answer to Kierkegaard’s provocative claim that “the ethical is as boring in life as it is in learning.” The first motif the author elaborates concerns the problem of the boringness of ethics in the perspectives of its history and of being melancholically overwhelmed with the scope of tradition (which results in melancholy). The problem in question is studied in keeping with the contrast between the melancholy of history and the ecstasis of postmodernity drawn by Agata Bielik-Robson. The second motif on which the author focuses is the role of boredom in understanding the origin of the category of melancholy as applied to the description of the human condition in contrast to the modern, reductive types of narration about the human being, for instance medically oriented psychoanalysis. The third motif developed in the article concerns the boringness of the normative detail and the contrasting trend to make general claims in ethics, as well as the difficulties the latter tendency entails. Then come the fundamental issues: firstly, the relation between conformity to ethics and unhurriedness, and, secondly, the reversal of the value traditionally attached to the categories of labour and idleness, which marks a difference between contemporaneity and antiquity. The Greek concept of schole and the weak and yet graspable link between the Greek term ethos and the Latin desidiabulum make it possible to restore the perspective in which unhurriedness, idleness and in a sense also boredom become the starting point of all reflectiveness, including normative reflection. Translated by Dorota Chabrajska